Lowering treatment temperature reduces salmon mortality: a new way to treat with hydrogen peroxide in aquaculture. Issue 3 (13th November 2017) - Overton, Kathy; Samsing, Francisca; Oppedal, Frode; Stien, Lars H; Dempster, Tim
Abstract: BACKGROUND: Hydrogen peroxide (H2 O2 ) baths are widely used to reduce numbers of salmon lice on farmed Atlantic salmon. Fish mortalities often occur after baths, with warmer temperatures increasing lethality. We tested whether mortality could be reduced and lice removal efficacy maintained by lowering bath temperatures relative to ambient temperatures. Post‐smolt salmon infected with lice were held at 10, 13 or 16 °C, and treated with 1.5 g/L H2 O2 for 20 min at equal or lower bath temperatures of 7, 10 or 13 °C. RESULTS: Salmon mortality decreased as ambient and bath temperatures decreased. No mortality occurred when fish at 13 °C were treated at 7 °C. For ambient temperatures of 16 °C, the number of lice remaining was reduced by four‐fold when treated at 7 °C compared with 13 °C. All treatments in which mortality was zero had similar efficacies regardless of bath temperature. CONCLUSION: We took salmon from warmer to colder temperatures to determine the optimum bathing temperature to prevent mortality. A temperature of 7 °C was optimal when treating with 1.5 g/L of H2 O2, as mortality was zero and pre‐adult lice removal was unchanged. By manipulating temperature, we developed a new method of H2 O2 bathing that reduces mortality. When ambient temperatures are >10 °C, we recommend that the industry decrease H2 O2 bath temperatures. © 2017 Society of Chemical Industry Abstract : Hydrogen peroxide is widely used in salmon delousing. We developed a novel method of lowering bath temperature during treatment to reduce treatment‐induced salmon mortality without compromising lice removal.